Mandados de criminalização decorrentes de tratados de direitos humanos - Passos, Jaceguara Dantas da Silva (2011)
The purpose of this study was to discuss the adherence of the Brazilian State to Human Rights treaties, the ensuing Criminalization Legal Precepts, and the corresponding legal consequences. As a signatory of a Human Rights Treaty, the Brazilian State is ruled through a legal system in line with the dictates of the Federal Constitution of 1988, whether or not said dictates are endorsed by the procedure laid out in Article 5, Section 3, of the Federal Constitution. By establishing provisions for the protection of new fundamental rights, treaties also constitute a parameter for the selection and protection of individual or collective legally protected values a form of protection regulated by Criminal Law, regardless of rule origin or hierarchy. This stems from the fact that by addressing the issue of Human Rights, the treaty should serve as a parameter for the protection of core values by Criminal Law, since the highest goal is the defense of human dignity a perspective in which any strictly formal, procedural hurdles must be overcome in order to achieve the highest good and interest of society and ensure the protection of said dignity, which constitutes the very core that informs and structures a Democratic State that abides by the Rule of Law. In order to guarantee the defense and protection of the human rights involved, Criminalization Legal Precepts are addressed, especially those related to Slavery, Child Labor, and Discrimination against Sexual Orientation, so as to impose limits to ordinary legislators in the definition of core values protected by Criminal Law, as well as to impose on the Brazilian State the obligation to criminalize conducts deemed offensive to certain legally protected values through the imposition of legal sanctions